2020
DOI: 10.1002/etc.4673
|View full text |Cite
|
Sign up to set email alerts
|

Toward Validation of Toxicological Interpretation of Diffusive Gradients in Thin Films in Marine Waters Impacted by Copper

Abstract: Determination of the median effective concentration (EC50) of Cu on Mytilus galloprovincialis larvae by diffusive gradient in thin films (DGT) has been shown to effectively reduce the need to consider dissolved organic carbon (DOC) concentration and quality. A standard toxicity test protocol was used to validate previously modeled protective effects, afforded to highly sensitive marine larvae by ligand competition, in 5 diverse site waters. The results demonstrate significant narrowing of M. galloprovincialis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…DGT-Cu concentrations were 31 and 34% of dissolved concentrations for 8 and 15 day deployments, respectively. This was in agreement with previous speciation analysis performed in this location (Gaulier et al, 2019), and consistent with the reduced lability of copper due to the presence of relatively strongly complexing organic ligands (Macoustra et al, 2019;Strivens et al, 2020). DGT-Mn and -Zn concentrations were 13~19%, and 47~57% lower than dissolved zinc concentrations measured in DWS, respectively.…”
Section: Metalssupporting
confidence: 92%
“…DGT-Cu concentrations were 31 and 34% of dissolved concentrations for 8 and 15 day deployments, respectively. This was in agreement with previous speciation analysis performed in this location (Gaulier et al, 2019), and consistent with the reduced lability of copper due to the presence of relatively strongly complexing organic ligands (Macoustra et al, 2019;Strivens et al, 2020). DGT-Mn and -Zn concentrations were 13~19%, and 47~57% lower than dissolved zinc concentrations measured in DWS, respectively.…”
Section: Metalssupporting
confidence: 92%
“…Copper is an essential element for all living organisms and play important roles in many metabolic processes (Ochoa-Herrera et al, 2011). However, copper may also be toxic to most species when concentrations exceed levels that are physiologically required (Strivens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…DGT-labile metal concentrations may represent the bioavailable metal fraction more accurately than filterable metal or total metal [ 23 , 24 ]. Therefore, it has been suggested that DGT-labile metal concentrations might represent the “potentially bioavailable” metal fraction to the biota [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%